PENONJOLAN TOKOH ANTAGONIS DALAM FILM THE DARK KNIGHT (Studi Semiotik Tokoh Joker dalam Film The Dark Knight) - Arif Budi Prasetya (Program Studi Ilmu Komunikasi FBIK Unissula, 2012)
semiotics is a study that examines the signs and meanings contained therein. These scien- tiï€ c developments are not only examines theÂ symbols contained in any society, but rather touch- ing aspects ofÂ construction and the cultural mindset behind it. This study tried to examine the semiotic aspects contained in the ï€ lm The Dark Knight and speciï€ cally examined an antagonist character of the Joker character. The Dark Knight is a genre ï€ lm with action and antagonistic character is the Joker. In this study, the Joker is considered as a symbol that represents a crime, and the symbol is shown through the character of the Joker. By using a semiotic analysis of Ro- land Barthes in which there are aspects of theÂ denotations and connotations that would result in the myth, this studyÂ intends to ï€ nd out how the Joker character in this ï€ lm is focused. The result is shown as the villain Joker through violent behavior, against the law and create chaos in the city of Gotham. Not only that, the Joker is a villain that is different from criminals in general, where he committed the crimeÂ instead of aiming for the money but only to an existence as a true villain. This is demonstrated through various scenes in the ï€ lm.